2018
DOI: 10.1007/s10157-018-1559-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between exercise intensity and renal blood flow evaluated using ultrasound echo

Abstract: RBF showed no significant decrease until 80% LaBP, and decreased with an increase in blood lactate. Reduction in RBF with exercise above the intensity at LaBP was due to decreased cross-sectional area rather than time-averaged flow velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Firstly, the transient decrease in peritubular capillary blood flow due to the reduction in renal blood flow induced by the exercise after the lactate acid breaking point may be associated with the increase in urinary L‐FABP excretion. This is because the previous study reported that the decreases in renal blood flow due to the exercise were induced after the lactate acid breaking point . Secondly, the post‐exercise albuminuria is also likely to be associated with the increase in urinary L‐FABP excretion.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Firstly, the transient decrease in peritubular capillary blood flow due to the reduction in renal blood flow induced by the exercise after the lactate acid breaking point may be associated with the increase in urinary L‐FABP excretion. This is because the previous study reported that the decreases in renal blood flow due to the exercise were induced after the lactate acid breaking point . Secondly, the post‐exercise albuminuria is also likely to be associated with the increase in urinary L‐FABP excretion.…”
Section: Discussionmentioning
confidence: 98%
“…This is because the previous study reported that the decreases in renal blood flow due to the exercise were induced after the lactate acid breaking point. 6 Secondly, the post-exercise albuminuria is also likely to be associated with the increase in urinary L-FABP excretion. The human L-FABPs gene expression and its urinary excretion have been reported to be increased by the protein overload in the proximal tubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The left UUO-treated kidney was observed using an ultrasound imaging system (Vevo2100; Fujifilm VisualSonics, Toronto, ON, Canada) on day 7. Left renal artery (RA) blood flow was estimated from velocity time integral (VTI), and left renal artery diameter (RAD) was calculated by PW-Doppler echo using Equation 2 38 : Statistical Analyses Two-group differences were analyzed by an unpaired t test.…”
Section: Ultrasonographymentioning
confidence: 99%
“…A previous review [38] reported that exercise could induce kidney damage, especially high-intensity exercise. Recently, some studies [39,40] suggested that the risk of kidney damage increases only when the exercise intensity exceeded the lactic acid threshold. However, no adverse events related to exercise were reported in any of the included trials.…”
Section: Different Exercise Intensities and Proteinuriamentioning
confidence: 99%